In Silico Analysis of Bioactive Compounds from Water Extract of Gelidium spinosum as COX-2 Inhibitor : In Silico Analysis of Bioactive Compounds from Water Extract of Gelidium spinosum - Warsi, Warsi; Jaswir, Irwandi (Clinical and Pharmaceutical Sciences Journal, 2026)
Water Extract of Gelidium spinosum (WEGs) contains various bioactive compounds which potential as anti-inflammatory agent. This study was aimed to predict anti-inflammatory potential of bioactive compounds from WEGs as COX-2 inhibitor through in silico analysis. The in silico analysis was conducted using AutoDock Vina. The protein originated from the Protein Data Bank, and the metabolites were gathered from PubChem. 2-Acetyl-3-methylbenzo[b]thiophene (1) (-7.1 kcal/mol), and ethyl p-methoxycinnamate (3) (-7.1 kcal/mol) were demonstrated a higher binding affinity compared with the other ligands and phenidone (-6.7 kcal/mol). Potential of these ligands were weaker than tolfenamic acid (-9.1 kcal/mol). According to this in silico analysis, bioactive compounds from water extract of G. spinosum possesses an anti-inflammatory potential mediated COX-2 receptor inhibition.